PENINGKATAN KETERAMPILAN LITERAS BACA TULIS MELALUI MEMBACA EKSTENSIF UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR TINGKAT TINGGI DI SEKOLAH DASAR - Nourma Yunita; Sri Suryanti; Sindy Ayu L.R; Nadia Putri L (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2023)
Students have speed reading skills are very important if they want to progress and develop and not be left behind with the current situation. With this skill, students will not be left behind in responding to the rapid flow of information and ideas that daily flood print and electronic media. How to improve extensive reading skills in order to improve thinking skills by using several methods including preview, read, review with jump reading techniques, The purpose of conducting this study is to analyze extensive reading skills, and analyze changes in high-level thinking patterns using several methods including preview, read, review with jump reading techniques in order to improve the thinking skills of grade V students at SD Muhammadiyah 1 GKB Gresik. The study uses the action research method which includes two cycles. Each cycle consists of four of them that are planned, actioned, observed, and reflected. To conduct data analysis carried out quantitatively and qualitatively, Extensive reading can be used several methods of preview, read, review with jump reading techniques to improve the ability of thinking grade V students at SD Muhammadiyah 1 GKB Gresik has run optimally. The research data carried out by the analysis, about increasing extensive reading skills using 3 preview, read, review methods with jump reading techniques is 15%. The result of the average value of the first cycle is 68.68 and the average value of the second cycle is 81.10. Conclusion of the average value of extensive reading skills to improve thinking skills using 3 methods preview, read, review with jumping reading techniques increased well. There is a change in the level of thinking skills and behavior that students show, namely students are increasingly excited, active, serious, and interested in extensive reading learning using 3 methods of preview, read, review with jump reading techniques